PROTOCOLOS DE INMUNOCASTRACIÓN Y SU EFECTO EN LA RENTABILIDAD EN CERDOS PIC (CAMBOROUGH X PIC 337) - Basurto Lass, Diana Lisbeth (2023)
The pork industry focuses on the breeding, reproduction and production of pigs, including all hygienic and genetic management, to obtain high-quality pork for human consumption. The research work was carried out at the Narcisita farm, located in the El Empalme Canton, El Guabo enclosure. With the objective of evaluating the immunocastration protocols and their effect on the profitability of Pic pigs (Camborough x Pic 337).